2014
DOI: 10.1002/ceat.201300849
|View full text |Cite
|
Sign up to set email alerts
|

Emission Source Characterization during an Ethylene Plant Shutdown

Abstract: To conduct a well‐planned plant shutdown, so as to reduce flare emissions for the sake of plant profitability and local environmental sustainability, one of the primary tasks is to perform comprehensive and precise accountings for flare emissions. Since the literature is still lacking systematic and quantitative studies, plant‐wide dynamic simulations are employed to simulate an ethylene plant shutdown and characterize its flare emission sources through which dynamic emission profiles of various emission speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, excessive flaring, especially the flaring during olefin plant startups, emits huge amounts of emissions: carbon dioxide (CO 2 ), carbon monoxide (CO), nitrogen oxides (NO x ), volatile organic compounds (VOC), highly reactive VOC (HRVOC, defined in Texas air quality regulation as ethylene, propylene, isomers of butene, and 1,3-butadiene), and partially oxygenated hydrocarbons (e.g., formaldehyde). These emissions may cause highly localized and transient air pollution events and negative societal impacts. For instance, HRVOCs have been identified to play a significant role in ground-level ozone formation in the HGB area (Houston–Galveston–Brazoria). According to Texas Administrative Code (TAC) title 30, chapter 115, subchapter H, industrial flaring emissions have been identified as the largest source for HRVOC emissions…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive flaring, especially the flaring during olefin plant startups, emits huge amounts of emissions: carbon dioxide (CO 2 ), carbon monoxide (CO), nitrogen oxides (NO x ), volatile organic compounds (VOC), highly reactive VOC (HRVOC, defined in Texas air quality regulation as ethylene, propylene, isomers of butene, and 1,3-butadiene), and partially oxygenated hydrocarbons (e.g., formaldehyde). These emissions may cause highly localized and transient air pollution events and negative societal impacts. For instance, HRVOCs have been identified to play a significant role in ground-level ozone formation in the HGB area (Houston–Galveston–Brazoria). According to Texas Administrative Code (TAC) title 30, chapter 115, subchapter H, industrial flaring emissions have been identified as the largest source for HRVOC emissions…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Lyondell Chemicals purportedly executed several FM procedures at its olefin sites. , Turnaround operations are usually modified by coupling some new FM plans; hence, detailed FM operation strategies are better to be virtually examined in advance to ensure operational safety and feasibility. In the past decade, dynamic simulations are largely employed to investigate the unit performance or serve as a platform to refine or optimize FM operation strategies during ethylene plant turnaround operations. …”
Section: Introductionmentioning
confidence: 99%